Can National Strategy Sidestep Civil and Political Rights? The Case of Indonesia’s Simultaneous Regional Elections - Bachtiar, Rizqi; Averos Aulia Ananta Nur (Human Rights in the Global South (HRGS), 2023)
The policy of transitioning to simultaneous elections in 2024 in Indonesia has given rise to polemics regarding human rights and democracy. There is no justification for the government to disregard citizens' civil and political rights in appointing interim regional heads. This research seeks to examine the phenomenon of the appointment of interim regional heads as an integral part of fulfilling citizens' civil and political rights. By using normative juridical or legal doctrinal research methods, this research demonstrates that the process of appointing interim regional heads is problematic. The government only relies on one regulation while ignoring the others, such as government and non-governmental organizations' recommendations. As a result, the appointment of interim regional heads appears less democratic, potentially leading to actions taken behind closed doors without involving public participation. This indicates that the centralized appointment of interim regional heads is more politically driven than merely focused on effectiveness and efficiency.